Effective biofilm control in a membrane biofilm reactor using a quenching bacterium (Rhodococcus sp. BH4) - Taskan, Banu; Hasar, Halil; Lee, Chung-Hak (Wiley, 2020)
The biofilm thickness in membrane biofilm reactors (MBfRs) is an important factor affecting system performance because excessive biofilm formation on the membrane surface inhibits gas diffusion to the interior of the biofilm, resulting in a significant reduction in the performance of contaminant removal. This study provides innovative insights into the control of biofilm thickness in O-2-based MBfRs by using the quorum quenching (QQ) method. The study was carried out in MBfRs operated at different gas pressures and hydraulic retention times (HRTs) using QQ beads containing Rhodococcus sp. BH4 at different amounts. The highest performance was observed in reactors operated with 0.21 ml QQ bead/cm(2) membrane surface area, 12 HRTs and 1.40 atm. Over this period, the performance increase in chemical oxygen demand (COD) removal was 25%, while the biofilm thickness on the membrane surface was determined to be 250 mu m. Moreover, acetate and equivalent oxygen flux results reached 6080 and 10 640 mg center dot m(-2)center dot d(-1) maximum values, respectively. The extracellular polymeric substances of the biofilm decreased significantly with the increase of gas pressure and QQ beads amount. Polymerase chain reaction denaturing gradient gel electrophoresis results showed that the microbial community in the MBfR system changed depending on operating conditions and bead amount. The results showed that the QQ method was an effective method to control the biofilm thickness in MBfR and provide insights for future research.
Keywords: biofilm control; biofilm formation; biofilm thickness; microbial community; quorum quenching